#TITLE_ALTERNATIVE# - OKTAVIANI (NIM 15304023), DWINA
Biowaste (biodegradable waste) is waste material capable of decomposing on anaerobic or aerobic conditions. Term used for biowaste is same with organic waste that more frequently used in waste treatment field. Biowaste management is a major problem arise in Bandung City. Based on PD Kebersihan Kota Bandung, 2005, solid waste volume of Pasar Induk Caringin is 1.22 liter/m2/day with composition of organic waste is 72.42%. The characteristic of biowaste in reactor was measured in Water Research Laboratory Environmental Engineering, ITB and biowaste that was used was fresh organic waste from Pasar Induk Caringin. Biowaste was sorted, shredded and blended by washing water with solid and liquid ratio was 1:1. Washing water which are used including tap water, tofu waste water, and Cikapundung River water. Biowaste that had been blended with water was fined by blender for 60 seconds. Then it was filtered by cloth to separate its solid and liquid phase. The solid phase will be degradated in three batch anaerobic reactors 2,5 liters volume by rumen cow bacteria and cow dungs with ratio 3 : 1 : 1. The lastest conditon, all of the reactor condition is mesophilic (about 23oC - 27oC). The pH of reactor I is about 4.91, water content 86.3%, volatile content 81.9%, ratio C/N 16 and C/P 50, oxygen gas content 4.01%, nitrogen gas 8.29%, methan gas 0,97% and CO2 gas 11.73%. Reactor II on pH condition 7.22, water content 88.9%, volatile content 79.9%, ratio C/N 16 and C/P 54, oxygen gas content 6.77%, nitrogen gas 83.28%, methan gas 2.66% and CO2 gas 7.30%. Whereas, reactor III have pH condition 6.87, water content 92.5%, volatile content 75.6%, and ratio C/N 19 and C/P 71, oxygen gas content 4.92%, nitrogen gas79.43%, methan gas4.91% and CO2 gas 10.74%. Until 96th day, degradation process still happen and all of reactors necessary post-treatment.